Modernity, religion, and the War on Terror - Winfield, Richard Dien, 1950- (Ashgate Pub., 2007)
States that the war on terror cannot be truly understood without investigating the legitimacy of modernity, the challenge that religion presents to modernization, and the post-colonial predicament from which Islamist reaction arises. This book illuminates the war on terror in light of these issues.